A phasor‐based approach to improve optical sectioning in any confocal microscope with a tunable pinhole. Issue 9 (10th June 2022) - D'Amico, Morgana; Di Franco, Elisabetta; Cerutti, Elena; Barresi, Vincenza; Condorelli, Daniele; Diaspro, Alberto; Lanzanò, Luca
Abstract: Confocal fluorescence microscopy is a well‐established imaging technique capable of generating thin optical sections of biological specimens. Optical sectioning in confocal microscopy is mainly determined by the size of the pinhole, a small aperture placed in front of a point detector. In principle, imaging with a closed pinhole provides the highest degree of optical sectioning. In practice, the dramatic reduction of signal‐to‐noise ratio (SNR) at smaller pinhole sizes makes challenging the use of pinhole sizes significantly smaller than 1 Airy Unit (AU). Here, we introduce a simple method to "virtually" perform confocal imaging at smaller pinhole sizes without the dramatic reduction of SNR. The method is based on the sequential acquisition of multiple confocal images acquired at different pinhole aperture sizes and image processing based on a phasor analysis. The implementation is conceptually similar to separation of photons by lifetime tuning (SPLIT), a technique that exploits the phasor analysis to achieve super‐resolution, and for this reason we call this method SPLIT‐pinhole (SPLIT‐PIN). We show with simulated data that the SPLIT‐PIN image can provide improved optical sectioning (i.e., virtually smaller pinhole size) but better SNR with respect to an image obtained with closed pinhole. For instance, two images acquired at 2 and 1 AU can be combined to obtain a SPLIT‐PIN image with a virtual pinhole size of 0.2 AU but with better SNR. As an example of application to biological imaging, we show that SPLIT‐PIN improves confocal imaging of the apical membrane in an in vitro model of the intestinal epithelium. Research Highlights: We describe a method to boost the optical sectioning power of any confocal microscope. The method is based on the sequential acquisition of multiple confocal images acquired at different pinhole aperture sizes. The resulting image series is analyzed using the phasor‐based separation of photons by lifetime tuning (SPLIT) algorithm. The SPLIT‐pinhole (SPLIT‐PIN) method produces images with improved optical sectioning but preserved SNR. This is the first time that the phasor analysis and SPLIT algorithms are used to exploit the spatial information encoded in a tunable pinhole size and to improve optical sectioning of the confocal microscope. Abstract : Schematic of the SPLIT‐PIN method: a stack of confocal images acquired with tunable pinhole size is processed by phasor analysis to produce a final image without out‐of‐focus background.